Exploitation of a Learner Corpus:Analysing Openings and Endingsin Academic Forums - Castillo Rodríguez, Cristina; Díaz Lage, José María (Opción, 2018)
The main aim of this paper is to analyse a learner corpus containingoriginal written productions in the compulsory forums created in a con-crete undergraduate subject. The reason for choosing the forum is that it isa space in which students can discuss in a more spontaneous way. The cor-pus compiled for this study will be managed with the corpus managementsoftware program AntConc. The study will be focused on the way thesestudents have contributed to the forums but paying special attention to theexpressions used in their openings and endings in written participations.
El objetivo principal de este trabajo es analizar un corpus de estu-diantes formado por textos escritos originalmente por estudiantes de gradoen varios foros puntuables. La razón por la cual se han elegido los forospuntuables reside principalmente en que estos son espacios en los que losalumnos pueden debatir de una forma espontánea. El corpus compiladopara este estudio se explotará por medio del programa de gestión de corpusllamado AntConc. El estudio se centrará en la forma en la que los alumnosparticipan en los foros con sus contribuciones prestando especial atencióna las expresiones utilizadas en los saludos y despedidas.
Keywords: corpus linguistics; learner corpus; forum; opening expres-sions; ending expressions; lingüística de corpus; corpus de estudiantes; foro; ex-presiones de saludo; expresiones de despedida; Scopus